New Insights toward the Acute Non-Thyroidal Illness Syndrome - MAIA, ANA LUIZA; Wajner, Simone M. (Frontiers in Endocrinology, 2012)
The non-thyroidal illness syndrome (NTIS) refers to changes in serum thyroid hormone levels observed in critically-ill patients in the absence of hypothalamic-pituitary-thyroid primary dysfunction. Affected individuals have low T3, elevated rT3 and inappropriately normal TSH levels. The pathophysiological mechanisms are poorly understood but the acute and chronic changes in pituitary–thyroid function are probably the consequence of the action of multiple factors. The early phase seems to reflect changes occurring primarily in the peripheral thyroid hormone metabolism, best seen in humans since 80-90% of the circulating T3 are derived from the pro-hormone T4. The conversion of T4-to-T3 is catalyzed by type 1 (D1) and type 2 (D2) deiodinases via outer-ring deiodination. In contrast, type 3 deiodinase (D3) catalyzes the inactivation of both T4 and T3. Over the last decades, several studies have attempted to elucidate the mechanisms underlying the changes on circulating thyroid hormones in NTIS. Increased inflammatory cytokines, which occurs in response to virtually any illness, has long been speculated to play a role in derangements of deiodinase expression. On the other hand, oxidative stress due to augmented reactive oxygen species (ROS) generation is characteristic of many diseases that are associated with NTIS. Changes in the intracellular redox state may disrupt deiodinase function by independent mechanisms, which might include depletion of the as yet unidentified endogenous thiol cofactor. Here we aim to present an updated picture of the advances in understanding the mechanisms that result in the fall of thyroid hormone levels in the acute phase of NTIS.